Early renin‐angiotensin system intervention is more beneficial than late intervention in delaying end‐stage renal disease in patients with type 2 diabetes. Issue 1 (27th November 2015) - Schievink, B.; Kröpelin, T.; Mulder, S.; Parving, H.‐H.; Remuzzi, G.; Dwyer, J.; Vemer, P.; de Zeeuw, D.; Lambers Heerspink, H. J.
Abstract : Aims: To develop and validate a model to simulate progression of diabetic kidney disease (DKD) from early onset until end‐stage renal disease (ESRD), and to assess the effect of renin‐angiotensin system (RAS) intervention in early, intermediate and advanced stages of DKD. Methods: We used data from the BENEDICT, IRMA‐2, RENAAL and IDNT trials that assessed effects of RAS intervention in patients with type 2 diabetes. We built a model with discrete disease stages based on albuminuria and estimated glomerular filtration rate (eGFR). Using survival analyses, we assessed the effect of RAS intervention on delaying ESRD in early [eGFR>60 ml/min/1.73 m 2 and albumin:creatinine ratio (ACR) <30 mg/g], intermediate (eGFR 30–60 ml/min/1.73 m 2 or ACR 30–300 mg/g) and advanced (eGFR <30 ml/min/1.73 m 2 or ACR >300 mg/g) stages of DKD for patients in different age groups. Results: For patients at early, intermediate and advanced stage of disease, whose mean age was 60 years and who received placebo, the median time to ESRD was 21.4, 10.8 and 4.7 years, respectively. RAS intervention delayed the predicted time to ESRD by 4.2, 3.6 and 1.4 years, respectively. The benefit of early RAS intervention was more pronounced in younger patients; for example, for patients with a mean age of 45 years, RAS intervention at early, intermediate or advanced stage delayed ESRD by 5.9, 4.0 and 1.1 years versus placebo. Conclusions: RAS intervention early in the course of proteinuric DKD is more beneficial than late intervention in delaying ESRD.